EVALUATING THE INTEGRATION OF ABCD BEHAVIORAL OBJECTIVES AND BLOOMS'S LEARNING DOMAINS IN THE MERDEKA CURRICULUM LESSON PREPARATION: INSIGHTS AND CHALLENGES - Adawiyah, Siti Rabiah; Kamilasari, Mila; Sulaeman, Dedi (Universitas Muhammadiyah Makassar, 2024)
Merdeka Curriculum has changed how teachers prepare the lessons. Leading to the necessary understanding of critical aspects of the teaching module making. This study characterizes the learning objectives of the Merdeka curriculum teaching module using Schwiers' ABCD behavioral objectives and Bloom's learning domains theory. It also explores the factors that hinder teachers from fully comprehending the three learning domains (cognitive, affective, and psychomotor) when designing a teaching module. This study utilized a qualitative approach with two junior high school teachers as participants. Analyzing the teaching modules and interviewing participants were performed. Using Schwiers' ABCD and Bloom's learning domains model, this study found that teachers had already focused on learner-centered activities. However, some inconsistencies arose in the presence of 'ABCD' components and three learning objectives statements. Factors like demotivation, lack of prior knowledge, insufficient practice and feedback, understanding gaps, time constraints, and overcrowded curriculum hindered teachers from applying the learning domains. In conclusion, integrating ABCD components and learning domains in a teaching module may facilitate effective instructional design, promote learner-centered approaches, set clear expectations, and optimize the learning environment.Merdeka Curriculum has changed how teachers prepare the lessons. Leading to the necessary understanding of critical aspects of the teaching module making. This study characterizes the learning objectives of the Merdeka curriculum teaching module using Schwiers' ABCD behavioral objectives and Bloom's learning domains theory. It also explores the factors that hinder teachers from fully comprehending the three learning domains (cognitive, affective, and psychomotor) when designing a teaching module. This study utilized a qualitative approach with two junior high school teachers as participants. Analyzing the teaching modules and interviewing participants were performed. Using Schwiers' ABCD and Bloom's learning domains model, this study found that teachers had already focused on learner-centered activities. However, some inconsistencies arose in the presence of 'ABCD' components and three learning objectives statements. Factors like demotivation, lack of prior knowledge, insufficient practice and feedback, understanding gaps, time constraints, and overcrowded curriculum hindered teachers from applying the learning domains. In conclusion, integrating ABCD components and learning domains in a teaching module may facilitate effective instructional design, promote learner-centered approaches, set clear expectations, and optimize the learning environment.